Determination of Factors Affecting Adolescents’ Healthy Lifestyle Behaviors and Self-Efficacy Levels According to the Health Promotion Model (Türkiye Sağlık Okuryazarlığı Dergisi, 2026)
Aim: This study aimed to determine the relationship between adolescents’ healthy lifestyle behaviors and self-efficacy levels, as well as the factors affecting this relationship. Methods: The study was completed between September 15 and October 15, 2020, with 816 adolescents aged 14-17, attending high school in a provincial center, who voluntarily participated. Data were collected using a “Descriptive Questionnaire” including socio-demographic information, the “Adolescent Lifestyle Scale,” and the “Self-Efficacy/Competence Scale.” Results: The mean score of the participants on the Adolescent Lifestyle Scale was found to be =104.07±19.23, and the mean score on the Self-Efficacy Scale was =84.78±14.32. A significant relationship was found between adolescents’ lifestyle behaviors and their self-efficacy levels. Based on the study results, school health policies should promote personalized interventions that enhance adolescents’ self-efficacy and address sociodemographic disparities to support equitable development of healthy lifestyle behaviors. Conclusion: It was concluded that factors such as adolescents’ role in health change and their self-definition of health affect adolescents’ healthy lifestyle behaviors.